Blended Learning System in Higher Education and Concerns of Students with Special Needs in Sri Lanka - Thasika, T.; Dilogini, S.; Grace, H.H. (Technological Advances in Science, Medicine and Engineering, 2023)
Purpose: Sri Lanka has been making significant improvements over the years to provide equal educational opportunities for all children at all levels and all stages of education after the progressive introduction of free education constitutions in the universal Free Education Policy in 1945and the Compulsory Education Policy in 1998. By incorporating upgraded disability inclusion in the National Disability Policy for Sri Lanka byprohibiting discrimination against students with special needs and disabilities. Currently, educational institutions worldwide are said to be usingblended learning methods to provide continuing education to students as an alternative to emergency closures, natural disasters, lockdowns, new normal, and socio-economic crises. Especially in Sri Lanka’s current economic crisis situation, blended learning continues to be analternative way to manage the cost of stationery, travel expenses, accommodation facilities at unreasonable prices, and even food and suppliesexcessive costs. As higher education is almost online, students with special needs experiencing this are life-threatening and unable to continuetheir higher education. Thus, the current study is designed to fill this gap by exploring students’ concerns about actual practices and therequirements that contribute to online and blended learning.